EÌszaki-Amerika. - Heckenast, Gustav, 1811-1878. (Heckenast GusztaÌv, 1864)
Map shows North and Central America, outlined areas of United States considered to be part of the Confederacy, the Union, and the states of Missouri, Kentucky, and Maryland as neither. Includes key to European claims in North America, key to volcanoes, and number key to New England states. Insets: "Az Aleuti Szigetcsoport" [Aleutian Islands]and "Kis AntillaÌk" [Lesser Antilles Keys/Islands]. Relief shown by hachures. Scale [1:20,000,000].